2017
DOI: 10.3174/ajnr.a5482
|View full text |Cite
|
Sign up to set email alerts
|

Combining Quantitative Susceptibility Mapping with Automatic Zero Reference (QSM0) and Myelin Water Fraction Imaging to Quantify Iron-Related Myelin Damage in Chronic Active MS Lesions

Abstract: Background and Purpose To quantify iron related myelin damage in chronic multiple sclerosis lesions with hyperintense susceptibility rim consistent with iron deposition compared to those without rim. Methods Forty-six patients had two longitudinal quantitative susceptibility mapping (QSM) with automatic zero reference (QSM0) scans with a mean interval of 28.9 ± 11.4 months. Myelin water fraction (MWF) mapping using fast acquisition with spiral trajectory and T2prep (FAST-T2) was obtained at the second time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 40 publications
8
40
2
Order By: Relevance
“…Using TSPO‐PET, it has been demonstrated that lesions with a rim of hyperintensity on QSM (rim+) have a significantly higher level of inflammation as compared with lesions lacking this rim (Fig 1A). 62 QSM rim+ lesions were also found to have more tissue injury, as measured by myelin water imaging 63 . The findings are consistent with other GRE studies showing that these paramagnetic rims indicate chronic active lesions, have lower signal intensity on T1‐weighted (T1‐w) MRI, 58 and can demonstrate slow expansion over time 52,64,65 .…”
Section: Neuroinflammation Beyond Acute Contrast Enhancing Lesionssupporting
confidence: 87%
See 1 more Smart Citation
“…Using TSPO‐PET, it has been demonstrated that lesions with a rim of hyperintensity on QSM (rim+) have a significantly higher level of inflammation as compared with lesions lacking this rim (Fig 1A). 62 QSM rim+ lesions were also found to have more tissue injury, as measured by myelin water imaging 63 . The findings are consistent with other GRE studies showing that these paramagnetic rims indicate chronic active lesions, have lower signal intensity on T1‐weighted (T1‐w) MRI, 58 and can demonstrate slow expansion over time 52,64,65 .…”
Section: Neuroinflammation Beyond Acute Contrast Enhancing Lesionssupporting
confidence: 87%
“…Most of the activated macrophages and microglia found at the rim of chronic active MS lesions contain iron, 51‐53 which causes a paramagnetic susceptibility shift and makes them visible on phase images generated from susceptibility‐weighted MRI at high field strength or on R2*/T2* maps generated from multi‐echo gradient echo (GRE) sequences 52,54‐59 . Quantitative susceptibility mapping (QSM) provides an effective means to directly map the distribution of susceptibility sources by solving the field‐to‐source inversion problem using a phase‐based magnetic field deconvolution technique 60‐63 . Using TSPO‐PET, it has been demonstrated that lesions with a rim of hyperintensity on QSM (rim+) have a significantly higher level of inflammation as compared with lesions lacking this rim (Fig 1A).…”
Section: Neuroinflammation Beyond Acute Contrast Enhancing Lesionsmentioning
confidence: 99%
“…This variability is unsurprising given the different imaging techniques, resolutions, and patient cohorts used in these studies. An imaging study on MS patients from our group revealed that 21% of lesions visible on QSM had a hyperintense rim, and 79% displayed homogenous or heterogenous distribution patterns ( 115 ). Our preliminary data from a combined imaging and histology study of MS brain tissue suggest that heterogenous QSM patterns were typically associated with the presence of heme within enlarged blood vessels in MS lesions.…”
Section: Qsm In Msmentioning
confidence: 90%
“…[5][6][7]11 This is in line with quantitative susceptibility mapping studies demonstrating increased susceptibility in rim-positive lesions as a marker of persistent inflammatory activity. 34,35 Combined 7 T/postmortem MRI studies reported a correlation between paramagnetic hypointense rims on SWI and iron accumulation in macrophages and microglia. [5][6][7] Interestingly, macrophages and microglia at the lesion edge expressed the proinflammatory markers CD86 6,7 and p22phox.…”
Section: Discussionmentioning
confidence: 99%